Pharmacokinetics of intravenous administered two different high doses of ascorbic acid in healthy beagle dogs - Lim, Seula; Oh, Ye In; Jeong, Jong Woo; Song, Kun Ho; Koo, Tae Sung; Seo, Kyoung Won (Journal of Advanced Veterinary and Animal Research, 2019)
Objective: We performed a randomized two-way crossover study to evaluate the pharmacokinetic profiles of two high-dose ascorbic acid (AA) after IV infusion in healthy beagle dogs. Materials and Methods: The dogs were administered IV AA at two doses of 1.5 and 3 gm/kg for 4 h, and the AA concentration in plasma and urine pH was measured before and after administration. Results: The plasma concentrations of AA in both groups peaked 3 h after administration. Among the two groups, the urine pH was not significantly different (p = 0.1299–0.7944). High-dose IV AA did not induce serious adverse events in dogs. Conclusion: The results of this study suggest that the high dose of AA which reaches the therapeutic dose for cancer and supports the safety of high-dose IV AA in dogs. J. Adv. Vet. Anim. Res., 6(4): 481-485, December 2019